2018
DOI: 10.1016/j.amjcard.2018.03.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Level of Vitamin D on Postoperative Atrial Fibrillation in Patients Undergoing Isolated Coronary Artery Bypass Grafting

Abstract: Objective: Postoperative atrial fibrillation (PoAF) is a common complication after coronary artery bypass grafting (CABG). The aim of the present study was to evaluate the association between development of PoAF and vitamin D levels in patients undergoing isolated CABG.Methods: This prospective randomized clinical trial was conducted on the patients with isolated CABG. The study was terminated when 50 patients in both PoAF(+) group and PoAF(-) group were reached. Development of AF until discharge period was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Among the studies included in this meta-analysis, only Shadvar et al [24] was unable to find a statistically significant difference between the groups. The other studies [21][22][23]25,26] demonstrated that preoperative vitamin D levels were independent predictors of POAF as assessed by univariate regression analysis. Also, Özsin et al, [21] Emren et al, [25] and Gode et al [22] found vitamin D to be an independent predictor according to the multivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Among the studies included in this meta-analysis, only Shadvar et al [24] was unable to find a statistically significant difference between the groups. The other studies [21][22][23]25,26] demonstrated that preoperative vitamin D levels were independent predictors of POAF as assessed by univariate regression analysis. Also, Özsin et al, [21] Emren et al, [25] and Gode et al [22] found vitamin D to be an independent predictor according to the multivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Cerit et al [23] 2017 41 87 + + -Retrospective Non-randomized Gode et al [22] 2016 15 75 + + + Prospective Non-randomized Özsin et al [21] 2018 50 50 + + + Prospective Randomized POAF: Postoperative atrial fibrillation; SR: Sinus rhythm +: Statistically significant; -: Statistically not significant. Only two of studies were randomized (Shadvar et al [24] and Özsin et al [21] ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations